Chemistry via Carnival: An Activity Based Approach in Learning Chemistry(Pembelajaran Kimia melalui Karnival: Pendekatan Pembelajaran Kimia Berasaskan Aktiviti) - Sim, S. F.; Lau, S.; Ngaini, Z. (Jurnal Pendidikan Malaysia, 2014)
This paper reports the experience of activity based learning conducted in Chemistry Carnival 2011 in Sarawak. The active learning oriented activities include hands-on experiments, quiz, poster and mini lectures were used to educate the school students some basics chemistry relating to daily life. Approximately 300 students attended the activities. Observations and questionnaires were used as the instruments to describe and measure the learning experience whether various activities have contributed to effective learning. Among these, hands-on experiments were found to be the most effective approach; more than 86% of the participants agree that they have learnt well from this peer mentoring and collaborative learning strategy. Posters, mini lectures and quiz however were relatively less favoured as they suffered some inherited shortcomings for example lecture is lacking in interactivity, poster and quiz similarly fall short in proactive involvement of participants. Activity based learning is an effective approach however it needs to be carefully constructed to achieve the learning outcomes.